Knowledge and practice related to Occupational Hazards among Maruti Cement Factory workers in Mirchaiya, Siraha, Nepal (Microbes and Health, 2016)
The main objective of the study is to find out the knowledge, practice and use of Personal Protective Equipments (PPE) among workers of cement factory limited located at Mirchaiya, Siraha, Nepal. We have tried to identify the various sources of information regarding occupational hazards, frequency of health visit in case of health problems or illness, hygiene practices among factory workers and socio-demographic characteristics like age, sex, marital status, income among the workers of cement factory. This is a descriptive cross-sectional study containing both qualitative and quantitative data. The primary data has been collected through semi-structured questionnaire assisted by researcher. Non-purposive sampling technique was used during the collection of data. Nearly three fourths of the respondents had satisfactory knowledge about occupational hazards. 86% workers responded as Tuberculosis to be the disease caused during work in cement factories. All the workers had some basic knowledge about PPE but only 33% of workers said that mask, gloves, boot and clothes fall under PPE. More than three fourths had knowledge regarding the effectiveness of the PPE. 96% of the total respondents used PPE during their working time. About 31% workers had been suffering from illness. 72% workers had a trend to visit doctor only in case of illness or if required. Only 82% workers had a trend to wash eyes with water only in case of dust present in eye. Similarly, only 78% workers had a practice of hand washing with water. And, only 4% of the co-workers had information regarding occupational hazards and use of PPE. We conclude that the variables having significant influence on the knowledge and practice of workers about occupational hazards were education, receiving information about the job-associated hazards, and attending a training course about occupational health and safety. These variables should be taken into consideration in any program addressing occupational health and safety issues in Nepal.